Комплексний підхід до визначення сутності фінансової стійкості промислового підприємства - Федоренко, Ірина Анатоліївна; Верещак, Віта Олександрівна; Яцишина, Анастасія Олегівна (Причорноморський науково-дослідний інститут економіки та інновацій, 2019)
У статті проаналізовано проблему пошуку сучасного підходу до обґрунтованого фінансово-економічного визначення сутності фінансової стійкості промислового підприємства. Визначено значення фінансової стійкості для окремих господарюючих суб’єктів, а також для економіки країни, отже, фінансова стійкість промислового підприємства відіграє надзвичайно важливу роль у забезпеченні сталого розвитку як окремих промислових підприємств, так й суспільства загалом. На основі аналізу наявних досліджень провідних учених сформовано визначення категорії «фінансова стійкість», яке відповідає сучасним вимогам, що висуваються промисловим підприємствам України. Виявлено основні ознаки поняття фінансової стійкості, які притаманні фінансовій стійкості промислового підприємства та дають змогу розкрити її фінансово-економічну сутність. Показано взаємозв’язок між видами стійкості промислового підприємства. На основі проведеного дослідження побудовано універсальний, ефективний та дієвий комплексний підхід до визначення фінансової стійкості промислового підприємства України, базою якого є абсолютні та відносні показники оцінювання фінансової стійкості.

The article analyzes the problem of finding a modern approach to the financial and economic definition of the essence of the financial stability of an industrial enterprise. In recent years, almost all industrial enterprises of Ukraine operate in a changing environment. For their effective and stable operation and financial and economic development, it is necessary, to constantly analyze financial stability. Thus, industrial enterprises that use information systems for effective management of financial stability can be sure that even in the unfavorable economic and political situation in the country they will be able to continue their work at the expense of their own reserves. It is revealed that the achievement of a stable financial condition of an industrial enterprise on the basis of effective capital management and movement of funds allows stable development in the existing market conditions of Ukraine in the long term. It is proved that the problem of financial stability management of industrial enterprises operating in the market economy of Ukraine is one of the most important not only financial but also General economic problems. The value of financial stability of individual economic entities for the economy and society as a whole is composed of its value for each individual element of the system. Based on the analysis of existing studies by leading scientists, the definition of the category of financial stability, which meets the modern requirements of industrial enterprises of Ukraine, is provided. The main features of the concept of financial stability, which is inherent in the financial stability of an industrial enterprise and allows revealing its financial and economic essence. It is proved that all types of financial stability of an industrial enterprise are interrelated and in the context of ensuring the effectiveness of activities on a strategic scale should become objects of constant monitoring by the management personnel of the industrial enterprise. It is concluded that only a comprehensive approach to the definition of financial stability, which is expressed by a system of relative and absolute indicators, will allow for its effective and efficient assessment for industrial enterprises in the changing environment of Ukraine.
Comprehensive approach to determining the essence of the financial stability of an industrial enterprise
Keywords: фінансовий стан; фінансові ресурси; платоспроможність; industrial enterprises; financial stability; financial condition